CD8α and CD70 mark human natural killer cell populations which differ in cytotoxicity - Rey, Camille; Jones, Katherine L.; Stacey, Kevin B.; Evans, Alicia; Worboys, Jonathan D.; Howell, Gareth; Sheppard, Sam; Davis, Daniel M. (Frontiers in Immunology, 2025)
Natural Killer (NK) cells are innate immune cells that can directly detect and kill cancer cells. Understanding the molecular determinants regulating human NK cell cytotoxicity could help harness these cells for cancer therapies. To this end, we compared the transcriptome of NK cell clones derived from human peripheral blood, which were strongly or weakly cytotoxic against 721.221 and other target cells. After one month of culture, potent NK cell clones showed a significant upregulation in genes involved in cell cycle progression, suggesting that proliferating NK cells were particularly cytotoxic. Beyond two months of culture, NK cell clones which were strongly cytotoxic varied in their expression of 28 genes, including CD8Α and CD70; NK cells with high levels of CD70 expression were weakly cytotoxic while high CD8Α correlated with strong cytotoxicity. Thus, NK cells were cultured and sorted for expression of CD70 and CD8α, and in accordance with the transcriptomic data, CD70+ NK cells showed low cytotoxicity against 721.221 and K562 target cells. Cytotoxicity of CD70+ NK cells could be enhanced using blocking antibodies against CD70, indicating a direct role for CD70 in mediating low cytotoxicity. Furthermore, time-lapse microscopy of NK cell-target cell interactions revealed that CD8α+ NK cells have an increased propensity to sequentially engage and kill multiple target cells. Thus, these two markers relate to NK cell populations which are capable of potent killing (CD70-) or serial killing (CD8α+).